Unlocking financing for small and medium-sized enterprises and entrepreneurship in Africa : empirical insights on the role of financial technology and financial deepening - Sanga, Bahati Joel (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.